Experimental investigation of syngas composition variation along updraft fixed bed gasifier. (1st October 2020) - Cerone, Nadia; Zimbardi, Francesco; Contuzzi, Luca; Baleta, Jakov; Cerinski, Damijan; Skvorčinskienė, Raminta
Highlights: Updraft gasification of almond shells with and without steam injection. Syngas composition along the gasifier height is reported for the first time. Molar ratio H2 /CO increased from 0.46 to 0.77 with steam addition. Tar production proportional with average temperature of gasifier, not gradients. Information about syngas composition and temperature important for modelling work. Abstract: Fixed bed gasification represents a convenient pathway for exploiting lignocellulose since it can be carried out on a small scale, while current technology is robust and fairly simple. Updraft gasifier is characterized by higher efficiency and is flexible towards feedstock, compared to the downdraft gasifier. The hydrogen to carbon monoxide ratio is the decisive parameter for determining syngas quality. Present contribution for the first time reports the evolution of the syngas composition at different heights of the reactive biomass bed in a pilot plant operating in a continuous mode, i.e. 20–30 kg/h of biomass feed. This was achieved by probing syngas streams directly from the core and analysing it onsite to measure the content of hydrogen, carbon monoxide, carbon dioxide, light hydrocarbons, nitrogen and oxygen, whilst the tar content was analysed offline. The addition of steam deeply affected the evolution of the chemical species and thermal profile. The syngas chemical composition was related to the thermal profile provided by in bed measurements of six thermocouples at the same locations. In the tests, almond shells were gasified with air or air and superheated steam mixture at equivalence ratio of 0.20 ± 0.01 and various steam to biomass ratios between 0 and 0.16 kg/kg. Addition of steam stabilized thermal profile inside the gasifier below 900 °C, improved the production of hydrogen up to 37.5 g/kg of biomass and the cold gas efficiency up to 72.5%. The use of steam positively affected the molar ratio of hydrogen to carbon monoxide that reached a steady value of 0.77 during the gasification operated at steam to biomass ratio of 0.11 kg/kg, versus the value of 0.46 measured in the corresponding test operated only with air. On the other hand, steam addition increased tar production up to 163 g/kg in air/steam gasification compared to the 137 g/kg with air gasification. Obtained data of the syngas composition along the bed height provide insight into the underlying physical and chemical phenomena and can be further used for the improvement and validation of gasification mathematical models.